Transformasi Layanan Administrasi Kependudukan Indonesia dalam Mewujudkan Konsep Welfare State: (Studi pada Dinas Kependudukan dan Pencatatan Sipil Kota Tangerang Selatan) - Hanif Hardianto (Universitas Serang Raya, 2022)
The transformation of public services in the field of population administration began to be felt after the all-internet or online era began to bloom in Indonesia. This causes public service providers to be asked to make changes in the concept of serving the community by following the changing times. The research method used is qualitative research or sociological juridical. The primary data source is interviews with the South Tangerang City Population and Civil Registry Service, while the secondary data source is various legal book materials and statutory regulations. The results of the research can be found that the transformation of Indonesian population administration services has begun to lead to realizing the concept of